The Whistleblowing Guide - Kenny, Kate; Vandekerckhove, Wim; Fotaki, Marianna (Ascent Audio, 2019)
The last five years have seen dramatic and fundamental changes in whistleblower procedures for organizations. Prompted by a spate of important public disclosures, organizations are now mandated by law to implement effective arrangements enabling employees to speak up about perceived wrongdoing. Currently few resources exist to help with this. To help fill the gap, The Whistleblowing Guide examines the opportunities and challenges associated with different types of whistleblowing and speak-up arrangements, making recommendations based on best practices you can trust. - Identifies the major organizational, structural, and cultural obstacles to speaking up through speak-up arrangements - Proposes effective whistleblowing and speak-up arrangements - Explains the specific policy and legislation requirements that can promote or impede the effective implementation of speak-up arrangements, and how these can be translated into commercial and public organizations across sectors and cultures - Makes a clear distinction between internal and external reporting arrangements.